Halych National Natural Park reservoirs vegetation syntaxonomy (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The phytocoenotical researches of Halych National Natural Park reservoirs vegetation have been made during 1998–2003 and 2007–2012. They differed on their origin and overgrowing degree. Dniester relict reservoirs and its branches, forests’ karst lakes, ponds and Burstyn reservoir, quarry reservoirs, areas with surface flooding soil were researched. 235 phytocoenotical descriptions have been done. Vegetation classifications were carried out by Brown-Blanke method. 37 syntaxones of association rank were pointed out. They belonged to 13 alliances, 5 orders, 3 classes. The coastal-water groups of Phragmito-Magnocaricetea class, specifically of Phragmitetum communis association, occupied the largest areas of every type reservoirs. Potametea class had the most syntaxonomy diversity. Its groups were common in the central part of relict lakes and less in artificial reservoirs. Lemnetea class groups were marked at shoals.
Keywords: Halych National Natural Park, reservoirs, hydrorhilous vegetation.